PENINGKATKAN MINAT DAN PRESTASI BELAJAR MATEMATIKA MELALUI PEMBELAJARAN MAKE A MATCH SISWA KELAS VII F SMP 1 BANGUNTAPAN - Hidayatullathifah Hidayatullathifah; A. A Sujadi (UNION: Jurnal Ilmiah Pendidikan Matematika, 2017)
The purpose of the study are (1) to describe the learning process by using Make a Match and (2) to increase students’ interest and learning of math achievement for class VII F at SMP 1 Banguntapan. The type of research was a Classroom Action Research (CAR) which was conducted in two cycles. The subjects of the study were the students of class VII F. It was consisted 27 students. The object of the study was students’ interest and the results of math achievement. The average percentage of students’ interest in the results of the questionnaire pre-cycle of 63,19%, in the cycle 1 increased 72,33%, in the cycle 2 increased 81,48%. At the beginning of the test's ability to use the average value of the daily tests of students in the second semester were 60,81 with the percentage of 11,11% achievement. in the first cycle increased 14,74 points increase in the amount of 75,55 with a percentage of 62,96%. In the cycle 2 increased 7,61 percentage points to 83,16 with 77,78% from minimum completeness criteria.